A Study of Inverse Problems Based on Two Kinds of Special Matrix Equations in Euclidean Space. (25th May 2014) - Huang, Rui; Wu, Xiaodong; Wang, Ruihe; Li, Hui
Abstract : Two special classes of symmetric coefficient matrices were defined based on characteristics matrix; meanwhile, the expressions of the solution to inverse problems are given and the conditions for the solvability of these problems are studied relying on researching. Finally, the optimal approximation solution of these problems is provided.